Impact of Company Characteristics, Liquidity, and Good Corporate Governance on Tax Aggression - Ismanto, Juli; Purnomo, Listiya Ike; Cahyani, Yenni; Rifai, Ahmad; Ruhiyat, Endang (EAJ (Economic and Accounting Journal), 2022)
This study aims to determine the impact of company characteristics, liquidity, and good corporate governance on tax aggressiveness. As secondary data, annual report information from companies included in the LQ45 index and listed on the IDX between 2016 and 2020 is utilized. The sample size was fourteen companies. The study used regression analysis of panel data as a methodology. The results indicated that the liquidity variables partially influenced tax aggressiveness, whereas the company's characteristics and good corporate governance did not. The test results suggest that if the liquidity level is low, it will reduce the level of creditor trust and result in a decrease in the level of capital loans by creditors; therefore, the company will maintain its liquidity level so as not to engage in tax avoidance.